Analisis Kinerja dan Dekomposisi Indeks Maqashid Syariah: Studi Pada Perbankan Syariah Periode 2015-2018 - Dwi Listiyorini; Maria Rio Rita (Universitas Islam Negeri Alauddin Makassar, 2020)
The purpose of this study is to (1) measure the performance of islamic banking in Indonesia which is included in the category of Sharia Commercial Banks (SCB) based on the Maqashid Sharia Index (MSI); (2) decompose the Maqashid Sharia Index into several components in Islamic Banking. This research uses descriptive quantitative research with the data source used is secondary data in the form of annual reports for the 2015-2018 period. The results of the discussion showed that the sharia banking that had the best performance in accordance with sharia principles was Bank BRI Syariah followed by Bank Victoria Syariah and BCA Syariah, whereas the lowest score is BNI Syariah. There is a weak positive correlations between education with justice, a very weak positive correlations between education with welfare, a very weak negative correlations between and justice with welfare.